The enactment of the counter-terrorism "Prevent duty" in British schools and colleges: beyond reluctant accommodation or straightforward policy acceptance. Issue 3 (3rd July 2019) - Busher, Joel; Choudhury, Tufyal; Thomas, Paul
ABSTRACT: When Britain imposed the "Prevent duty", a legal duty on education, health and social welfare organisations to report concerns about individuals identified as at-risk of radicalisation, critics argued it would accentuate the stigmatisation of Muslim communities, "chill" free speech, and exacerbate societal securitisation. Based on 70 interviews with educational professionals and a national online survey (n = 225), this article examines their perceptions of how the duty has played out in practice. It then provides an explanation for why, contrary to expectations, not only has overt professional opposition been limited, but there has been some evidence of positive acceptance. It is argued that these findings neither simply reflect reluctant policy accommodation nor do they simply reflect straightforward policy acceptance, but rather they comprise the outcome of multi-level processes of policy narration, enactment and adaptation. Three processes are identified as being of particular importance in shaping education professionals' engagement with the duty: the construction of radicalisation as a significant societal, institutional and personal risk; the construction of continuity between the Prevent duty and existing professional practices; and the responsibilisation of first-line professionals. The conclusion reflects on the wider public and policy implications of these findings.